What should I know before engaging in recreational activities/training? - Vuksanovikj, Vladimir; Jovanovski, Jovan; Aceski, Aleksandar (Faculty of physical education sport and health, 2016)
Prior to engaging yourself in certain sport activity as a form of recreation, it shall be necessary to collect information on your capacities, on what can be expected from the chosen activity, as well as on the manner in which the body shall behave during or after trainings. We most often consume both time and energy without even knowing the processes that our body and mind go through. It is rather interesting to become familiar with the energy depots used by the body for “fuel” during certain load intensity. Therefore, in this text, one shall find information which shall, at least, to some extent, bring closer the practice process (for the beginners), which might help in terms of knowing what to expect from the training without simply feeling fatigue and regard the next training with mistrust.
Keywords: exercise; training; recreation; aerobic; anaerobic